Example Jupyter notebook illustrating how mdciao can be used in API mode. - Guillermo Pérez-Hernández (21156182) (2025)
In this case we compute the Gα-β2AR-interface contact frequencies. The 12 notebook cells are shown in two panels next to each other, A) cells [1] to [7] and B) cells [8] to [12]. The outputs of cells [3] and [5] have been edited out ([…]) but are analogous to Fig 2A) and can be found in the online documentation and the S1 Notebook. The main computation is the generation of the mdciao object, intf, in cell [5] which can later be used to generate multiple text, tabular, and graphic reports of the frequencies, distributions, and time-traces anywhere else in the notebook. A full version of this notebook, with full outputs and high-res pictures can be found in the S1 Notebook, and an online version can be found at https://proteinformatics.uni-leipzig.de/mdciao/gallery.html#examples. Locally, mdciao users can access this notebook (and others) by invoking the CLT mdc_notebooks.py (cf. Table 1).